2015
DOI: 10.1111/ejh.12584
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of porcine anti‐human lymphocyte globulin and rabbit anti‐human thymocyte globulin in the treatment of severe aplastic anemia: a retrospective single‐center study

Abstract: The efficacies, survival, and safety profiles of pALG-based treatments are similar to or even better than those of rATG-based treatments. These results may help guide the clinical use of pALG in immunosuppressive therapy for SAA.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
7
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(8 citation statements)
references
References 27 publications
1
7
0
Order By: Relevance
“…Liu et al [ 21 ] retrospectively analyzed SAA patients treated with either P-ALG (n = 43) or R-ATG (n = 32) plus CSA, and suggested there were no significant difference in 2-year OS between the 2 groups (87.4% ± 6.2% vs 83.2% ± 7.8%, P = 0.493). Other studies [ 10 , 11 ] comparing the efficacy of P-ALG and R-ATG in the IST treatment showed similar results.…”
Section: Discussionsupporting
confidence: 52%
See 1 more Smart Citation
“…Liu et al [ 21 ] retrospectively analyzed SAA patients treated with either P-ALG (n = 43) or R-ATG (n = 32) plus CSA, and suggested there were no significant difference in 2-year OS between the 2 groups (87.4% ± 6.2% vs 83.2% ± 7.8%, P = 0.493). Other studies [ 10 , 11 ] comparing the efficacy of P-ALG and R-ATG in the IST treatment showed similar results.…”
Section: Discussionsupporting
confidence: 52%
“…However, horse ATG is not available in China, while a new porcine anti-lymphocyte globulin (P-ALG) is available. Several studies have compared the efficacy and safety of R-ATG and P-ALG in IST and suggested that P-ALG was similar to or even better than R-ATG [ 9 11 ]. In addition, P-ALG containing conditioning regime before HSCT in the setting of MSD-HSCT and MUD-HSCT have also demonstrated good efficacy and tolerance [ 12 , 13 ].…”
Section: Introductionmentioning
confidence: 99%
“…Zhang et al [34] demonstrated that the half-life of R-ATG was 29.7 ± 2.60 days and the effective serum concentration of R-ATG was maintained for at least 90 days in vivo. Ma et al [35] compared the safety and efficacy of P-ATG with R-ATG in SAA and found the lymphocyte count decreased in both groups, whereas the R-ATG group had a longer time of lymphocyte decrease and lower lymphocyte counts. They then further compared the changes in subsets of T cell until 6 months after the treatment and found the inhibitory effects on the CD8 + T cells were not significantly different between the 2 groups, whereas the inhibitory effects on CD4 + T cells were significantly stronger in the R-ATG group than in the P-ATG group.…”
Section: Discussionmentioning
confidence: 99%
“…While Chinese patients only have access to rabbit and porcine ATG. The porcine form is more widely used and promoted due to its good efficacy, safety, and low price (34)(35)(36). Recent articles (36)(37)(38)(39) have reported that the overall response and survival rates of AA patients using standard IST with porcine ATG plus CsA are neither better nor worse than those with rabbit ATG.…”
Section: Discussionmentioning
confidence: 99%